THE MEANING OF TERMINOLOGY. TERMS AND ITS FORM IN LINGUISTICS - Tilloyeva, Namuna (Educational Research in Universal Sciences, 2022)
This article is devoted the stages of terminology and its role in linguistic in which aims to identify structural features of linguistics terms in language. Moreover, it describes development of terminology and its origin meaning also what is the terminology itself